Partisipasi Masyarakat terhadap Penyelenggaraan Pendidikan Anak Usia Dini Di Desa Parinding - Agusriani, Ade; Fitri (Jambura Early Childhood Education Journal, 2024)
Community participation in early childhood education is important because it will support the success of early childhood education. This study aims to determine efforts to increase community participation in the implementation of early childhood education in Parinding Village and obstacles in increasing community participation in implementing early childhood education in Parinding Village, Baraka District, Enrekang Regency. This type of research is classified as qualitative research with a phenomenological approach. The data sources are the head of Parinding Village, the head of the Kindergarten, the Kindergarten Committee, the head of the Kindergarten Foundation and community leaders and parents of students. Data collection methods used are observation, interviews and documentation. The data obtained is then processed using data processing and data analysis techniques through three stages, namely: data reduction, data display and data verification. The results of the study show that efforts to increase community participation in the implementation of early childhood education are; 1) Involve parents of students in supporting learning programs in kindergarten; 2) Carry out outreach activities; 3) Involve the parents of students in the implementation of parenting. Meanwhile, the inhibiting factors in increasing community participation in the implementation of early childhood education are; 1) The factor of ignorance and lack of understanding of parents; 2) Low education factor; 3) The factor of lack of socialization; 5) Low economic factors; 6) The busy factor of the community.